Evaluasi Kepuasan Pengguna Sistem Informasi Akademik Menggunakan Metode End User Computing Satisfaction - Prama Dita Laura; Yana Khairun Nisak D; Dori Gusti Alex Candra; Atika Fauziyyah; Leonard Tambunan; Jufri Jufri (Jurnal Sains dan Teknologi Informasi, 2026)
Digital transformation in higher education requires academic data management that is not only technically functional but also capable of satisfying its users. This study aims to evaluate user satisfaction with the Academic Information System (SIAKAD) at Mitra Gama Institute of Technology using the End User Computing Satisfaction (EUCS) framework. The research method used was descriptive quantitative, involving 28 active user respondents selected through purposive sampling. The evaluation was conducted across five main dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. Data were collected using a Likert-scale questionnaire that had been validated using Pearson’s correlation and tested for reliability with Cronbach’s Alpha (0.947). The analysis results showed that user satisfaction levels varied across each dimension. The Content dimension received the highest score of 71.42%, followed by the Accuracy dimension at 60.72%, both of which fell into the “good” category. However, the Format dimension recorded the lowest score of 53.55%, rated as “fair,” indicating significant complaints regarding the user interface, which was deemed unresponsive and rigid. Meanwhile, the Timeliness dimension scored 43.74% and Ease of Use scored 41.97%. The study’s findings concluded that while SIAKAD has functionally been able to provide relevant content, there is an urgent need to improve visual aesthetics, navigation flow efficiency, and server performance stability—especially during peak access periods. The proposed strategic recommendations include migrating to a more modern interface design and optimizing real-time data synchronization to holistically enhance the user experience.